The effects of 2100‐MHz radiofrequency radiation on nasal mucosa and mucociliary clearance in rats. Issue 7 (16th April 2015) - Aydoğan, Filiz; Aydın, Emine; Koca, Gökhan; Özgür, Elçin; Atilla, Pergin; Tüzüner, Arzu; Demirci, Şule; Tomruk, Arin; Öztürk, Göknur Güler; Seyhan, Nesrin; Korkmaz, Meliha; Müftüoğlu, Sevda; et al.
<x xml:space="preserve">Abstract</x> Background Nasal mucociliary clearance has an important role in voiding the airways from inhaled foreign substances. This activity could be disturbed by environmental factors such as radiofrequency radiation. The aim of the present study was to investigate short‐term and relatively long‐term effects of 2100‐MHz radiofrequency radiation emitted by a generator, simulating a 3G‐mobile phone, on the nasal septal mucosa and mucociliary clearance in rats. Methods Thirty Wistar albino rats were divided into 4 groups. There were 6 rats in Group A and Group B, which served as the control groups (10‐day and 40‐day groups, respectively). Groups C (10‐day exposure) and D (40‐day exposure) were both composed of 9 rats; they comprised the radiofrequency radiation exposure groups. The rats in groups C and D were exposed to 2100‐MHz radiofrequency radiation emitted by a generator, simulating a 3G‐mobile phone, 6 hours/day, for 10 or 40 days, respectively. After exposure, nasal mucociliary clearance was measured by rhinoscintigraphy. After euthanization, the nasal septa of the animals were removed, and tissue samples of the nasal mucosa were examined using a transmission electron microscope. Results The differences in mucociliary clearances between groups A and C, groups B and D, and groups C and D were found to be statistically significant (p = 0.005, p < 0.001, p < 0.001, respectively). Although there were no histopathological abnormalities in the control groups, the exposure groups showed a number of degenerated and apoptotic cells, ciliary disorganization and ciliary loss in the epithelial cells, epithelial metaplasia, alteration of normal chromatin distribution and karyolysis in nuclei, changes in the basal cells, and lymphocytic infiltration. The histopathological changes were more severe in group D. Conclusion Radiofrequency radiation at 2100 MHz damaged the nasal septal mucosa, and disturbed the mucociliary clearance. Ciliary disorganization and ciliary loss in the epithelial cells resulted in deterioration of nasal mucociliary clearance.